Tailings management handbook : a life-cycle approach - Morrison, Kimberly Finke (Society for Mining, Metallurgy & Exploration (SME), 2022)
"Tailings Management Handbook is the only comprehensive resource rooted in new fundamentals and global principles for tailings management. The book focuses on the basics, life-cycle planning, site and tailings characterization, tailings storage facility design and construction, as well as systems and operations of tailings storage facilities. It also includes 42 real world case studies"--